Intra-and International Risk-Sharing in the Short Run and the Long Run - Sascha O. Becker; Mathias Hoffmann (Center for Economic Studies and ifo Institute (CESifo), 2003)
We investigate empirically how industrialized countries and U.S. states share consumption risk at horizons between one and thirty years. U.S. federal states share about 50 percent of their permanent idiosyncratic risk through cross-state capital income flows. While insurance against transitory fluctuations in output is virtually complete, OECD countries do not share any of their permanent idiosyncratic risk. Our results suggest that purely transaction cost based theories cannot explain the home bias, since the potential welfare gains from insurance against permanent shocks would by far outweigh that of insuring against transitory variation. We conclude that permanent and transitory shocks constitute two qualitatively different kinds of risk and that various forms of endogenous market incompleteness may render permanent shocks a lot harder to insure, in particular at the international level.
Keywords: 330; consumption risk sharing; home bias; international business cycles; panel vector autoregressions